ALGORITMA GENETIKA UNTUK PENYELESAIAN TRAVELLING SALESMAN PROBLEM PADA RUTE PENDISTRIBUSIAN BARANG SICEPAT EKSPRES - Br Surbakti, Elesa Jessy; Syahmarani, Aghni (Universitas Islam Sumatera Utara, 2024)
This study aims to examine the application of genetic algorithms in solving the Traveling Salesman Problem (TSP) on the distribution route of goods at SiCepat Ekspres, especially in Medan City. Limiting the research area to Medan City and involving 7 branch warehouses as destination points, the genetic algorithm found the shortest route of 72.6 km. In this study, the mutation process is limited to genes of the 3rd to 7th order to reduce the possibility of damaging an already good solution, thus maintaining the quality of the solution while still providing opportunities for further improvement. The results show that the genetic algorithm can provide an efficient shortest route solution, so that it can help improve the efficiency of goods distribution at SiCepat Ekspres.